Mechanics of a pressurized penny-shaped crack in a poroelastic halfspace. (1st June 2021) - Selvadurai, A.P.S.; Samea, P.
Abstract: This paper examines the axisymmetric problem of a penny-shaped crack located in a poroelastic halfspace that is modelled by Biot poroelasticity. The paper first examines the axisymmetric problem of the mechanics of fluid injection over a circular area within a halfspace that would create the skeletal stress state necessary to initiate fracture. The triggering of the fracture is assumed to create an axisymmetric penny-shaped crack whose surfaces will be subjected to fluid pressure. The mechanics of the penny-shaped crack in terms of its potential to extend in an axisymmetric fashion is examined by formulating the poroelastic mixed boundary value problem and solving the coupled Fredholm integral equations of the second-kind obtained through successive applications of integral transform techniques. The analysis of the poroelasticity problem of fluid-injection into the crack gives rise to time-dependent skeletal stress intensity factors (SIFs) at the crack tip; these are combined with a mixed-mode brittle skeletal fracture criterion to establish the injection pressures that can lead to the extension of the penny-shaped crack in a self-similar fashion.